The Public Transport Crisis in South Africa: Through the Eyes of the Four Revolutions - Mondli Hlatshwayo (The Thinker, 2022)
Debates on the Fourth Industrial Revolution have tended not to focus on the direct relationship between all four technological revolutions and transportation – a crucial element of all technological surges. At the same time, scholarship on transportation has generally ignored the significance of transportation in all the revolutions. This article therefore seeks to strike a balance between these two extremes by showing that all the technological revolutions were also about transportation. In other words, the debates on the technological advances provide scholars, researchers, engineers, and working-class organisations with the space to foreground transport as an issue requiring special attention, especially in South Africa where the public transport system faces many challenges. Critically applying the prism of the four industrial revolutions, the article demonstrates that South Africa lags behind from a transport perspective, and still relies on the transportation of the Second Industrial Revolution when other countries are utilising technologies of the Fourth Industrial Revolution. Compounding matters is that even transport technologies invented in the 1800s are being stolen and vandalised, and the maintenance of the system is extremely poor. The article then submits that these transport problems may be solved by mobilisation and advocacy led by working-class and poor communities negatively affected by the crisis.